A Parent Company’s Liability for Anti-Monopoly Damages to its Subsidiary’s Creditors Considering the New Regulations of Corporate Groups - Wieczerzyńska, Beata (Review of European and Comparative Law, 2022)
The operations of a corporate group managed by a parent and guided by a shared strategy and interests of the group may in some cases cause damage to a subsidiary’s creditors. This study will in particular focus on the liability towards creditors for anti-monopoly damages caused by a breach of competition laws and not resulting from the binding orders of a parent company to its subsidiary. It is especially important to establish if and possibly how a parent’s liability arises for antimonopoly damages to its subsidiary’s creditors where it’s not related to a binding order, considering the special regulations of liability for damages caused by breaches of competition laws in the context of the new regulations of corporate groups.